2018
DOI: 10.1371/journal.pone.0204407
|View full text |Cite
|
Sign up to set email alerts
|

Variable pollen viability and effects of pollen load size on components of seed set in cultivars and feral populations of oilseed rape

Abstract: Pollination success is important for crop yield, but may be cultivar dependent. Less is known about which floral traits influence pollination success. Floral traits, e.g. traits related to attraction and reward, can also contribute to gene flow via pollen, the latter being of particular importance in oilseed rape (Brassica napus) where gene flow occurs between plants of crop, volunteer and feral origin as well as related taxa. We investigated the relationship between pollen load size and seed set in winter oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In a previous study on pollen germination rate and pollen tube growth rate, Lankinen et al (2018) found larger variation within five feral populations and seven cultivars of OSR than between these two groups. They demonstrated that only one cultivar showed significantly higher pollen performance than one feral population.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In a previous study on pollen germination rate and pollen tube growth rate, Lankinen et al (2018) found larger variation within five feral populations and seven cultivars of OSR than between these two groups. They demonstrated that only one cultivar showed significantly higher pollen performance than one feral population.…”
Section: Discussionmentioning
confidence: 68%
“…Feral oilseed rape may also need to allocate resources to other functions than pollen since they grow in less favorable conditions than the crop plants. However, when crop cultivars and ferals were compared, there was no difference in pollen viability (Lankinen et al 2018).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Fujii and Ohmido ( 2011 ) reported that RS plants with low pollen fertility contain aberrant chromosome fragments in somatic cells. Evaluation of pollen viability is an important characteristic of the genotype because the ability to pollinate is one of the basic selection features in plant breeding processes (Lankinen et al 2018 ). RS plants originating from interspecific crosses between B. rapa and B. oleracea are usually self-incompatible, a feature transferred from the parental species.…”
Section: Discussionmentioning
confidence: 99%
“…When pollen grains land on the stigma, another factor that plays an important role in fertilization is the genotype of the pollen donor. Evidences are accumulating, suggesting that fertilization is not always a random process [34] and that mate choice occurs in numerous plant species [35][36][37][38][39][40][41][42][43][44][45][46]. Pollen competition is estimated to be higher in outcrossing than in selfing plants because pollen load in outcrossers is expected to be genetically more diverse [47].…”
Section: Introductionmentioning
confidence: 99%